Healthy days at home: A population‐based quality measure for cancer patients at the end of life. Issue 22 (10th August 2021) - Lam, Miranda B.; Riley, Kristen E.; Zheng, Jie; Orav, E. John; Jha, Ashish K.; Burke, Laura G.
Abstract : Background: Healthy Days at Home (HDAH) is a novel population‐based outcome measure. In this study, its use as a potential measure for cancer patients at the end of life (EOL) was explored. Methods: Patient demographics and health care use among Medicare beneficiaries with cancer who died over the years 2014 to 2017 were identified. The HDAH was calculated by subtracting the following components from 180 days: number of days spent in inpatient and outpatient hospital observation, the emergency room, skilled nursing facilities (SNF), inpatient psychiatry, inpatient rehabilitation, long‐term hospitals, and inpatient hospice. How HDAH and its components varied by beneficiary demographics and health care market were evaluated. A patient‐level linear regression model with HDAH as the outcome, hospital referral region (HRR) random effects, and market fixed effects were specified, as well as beneficiary age, sex, and comorbidities as covariates. Results: The 294, 751 beneficiaries at the EOL showed a mean number of 154.0 HDAH (out of 180 days). Inpatient (10.7 days) and SNF (9.7 days) resulted in the most substantial reductions in HDAH. Males had fewer adjusted HDAH (153.1 vs 155.7, P < .001) than females; Medicaid‐eligible patients had fewer HDAH compared with non‐Medicaid–eligible patients (152.0 vs 154.9; P < .001). Those with hematologic malignancies had the fewest number of HDAH (148.9). Across HRRs, HDAH ranged from 10.8 fewer to 10.9 more days than the national mean. At the HRR‐level, home hospice was associated with greater HDAH, whereas home health was associated with fewer HDAH. Conclusions: HDAH may be a useful measure to understand, quantify, and improve patient‐centered outcomes for cancer patients at EOL. Abstract : Healthy Days at Home is a population‐based quality measure that may be useful for cancer patients at the end of life. It may allow providers and policymakers to understand, quantify, and improve patient‐centered outcomes for this population.